دراسة تأثير الأشعة فوق البنفسجية على الخصائص الميكانيكية لنماذج من السيور المطاطية المفلكنة - ميساء شاش (Tishreen University, 2016)
يتضمن البحث دراسة تجريبية لمعرفة تأثير الأشعة فوق البنفسجية (أشعة UV) على السلوك الميكانيكي للسيور المطاطية المفلكنة المستخدمة في عمليات النقل المختلفة، وبشكل خاص السيور المستخدمة في معمل اسمنت طرطوس، من خلال تحضير عينات مختلفة من هذه السيور وتعريضها لأشعة UV لفترات زمنية مختلفة، ومن ثم اختبارها على الشد وعلى الاهتراء. وقد تمت مقارنة النتائج مع عينات مماثلة للعينات المختبرة لم تتعرض لأشعة UV، كما تمت المقارنة مع عينات تم تسخينها بالفرن، وذلك من أجل الوصول إلى الشروط المثالية لاستخدام هذه السيور الذي يضمن فترة استخدام أطول وبشروط آمنة. وأظهرت الدراسة أن للأشعة فوق البنفسجية أثر على زيادة معدل الاهتراء، وكذلك على زيادة قوة الشد الطولية للسيور المدروسة. حيث أن زيادة قوة الشد الطولية تزيد من معدل الاهتراء لهذه السيور. This study includes an experimental work to determine the effect of ultraviolet radiation (uv-rays) on the mechanical behavior of the conveyor rubber vulcanizing, which used in various transport operations, and in the cement plant Tartus. In this work, it has been prepared different samples of belts, and they were exposed to uv radiation at differente times, then they were tested to know its wear and tensile strength. The results were compared with samples similar to the samples tested, which was not exposed to the rays of UV, and with other samples exposed to temperatures, and that in order to reach the ideal conditions for the use of these belts, which ensures longer period of use and safe conditions. This study showed that uv-rays increase the average of wear and the tensile strength of belts.